PERTANGGUNGJAWABAN NATO TERHADAP PELANGGARAN KEWAJIBAN INTERNASIONAL MENURUT HUKUM INTERNASIONAL - Zainal Abdul Aziz Hadju; Irawati Handayani (Arena Hukum, 2022)
The accountability of subjects of international law has undergone rapid development, in particular to the accountability of international organizations. This study intends to analyse the legality of NATO’s humanitarian interventions in Libya and also analyse NATO’s accountability for violations of international law. The research method used is normative research with a statutory approach, a case approach, and a comparative approach. The results showed that violations committed by NATO member states can be attributed to NATO as an international organization. NATO has committed violations of international obligations under articles 3, 4 and 61 of the DARIO. NATO accountability as stipulated in articles 30-31 and 41-42 of the DARIO can be carried out by ceasing to commit violations and avoiding such acts in the future, as well as giving compensation for damages caused.